Study of Dynamic Brittle Fracture of Composite Lamina Using a Bond-Based Peridynamic Lattice Model - Jushang Guo; Weicheng Gao; Zhenyu Liu; Xiongwu Yang; Fengshou Li (Advances in Materials Science and Engineering)
We proposed a bond-based peridynamic lattice model for simulating dynamic brittle fracture of 2D composite lamina. Material orthogonal anisotropy was represented by rotating topological lattice structure instead of fiber directions. Analytical derivation and numerical implementation of the proposed model were given based on energy equivalence. Benchmark composite lamina tests are used to validate the capability of modeling dynamic fracture of the method. The peridynamic lattice model is found to be robust and successful in modeling dynamic brittle fracture of 2D composite lamina and can be extended to composite laminates by applying 3D lattice structure.